Teaching English Using Two Stay Two Stray in Improving Students' English Speaking Skills Integrated with Foreign Language Anxiety - Jupri Jupri; Mismardiana; Muslim; Haerazi Haerazi (Journal of Language and Literature Studies, 2022)
This research investigated the teaching of English by using Two Stay Two Stray to improve the students’ speaking skill in the 10th-grade students of vocational schools, West Nusa Tenggara Province, Indonesia. The participants of this research were 28 students. The research utilized a classroom action research. The research covered two cycles and each cycle consisted of four steps they were; planning, acting, observing, and reflecting. The research consisted of two cycles, and each cycle applied three parts, such as; pre-test, treatment, and post-test. The data collected were qualitative and quantitative data. The qualitative data were gained through observation and documentation. Meanwhile, the quantitative data was collected from the test. The researcher used SPSS 16.00 to analyze the quantitative data. The researcher found a significant improvement in students’ speaking skills after giving treatment using Two Stay Two Stray in cycle I and II. The improvement of using Two Stay Two Stray in improving the students’ speaking skill was significant. It can be seen from cycle I up to the cycle II. The result of the cycle I showed that the mean of post-test is higher than the the pre-test. The mean of the post-test was 66.14 and pre-test are 60.50. In cycle II, the mean of the post-test is higher than the mean of the pre-test. The mean score of post-test was 76.28 and pre-test are 66.14. The researcher concluded that using Two Stay Two Stray improved the 10th grade students’ speaking skill at vocational schools, West Nusa Tenggara Province.